PENGARUH CLIENT IMPORTANCE, TENURE AUDIT, ROTASI AUDIT DAN FEE AUDIT TERHADAP KUALITAS AUDIT DAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN KEUANGAN YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2013 2017) - Wadri Wahyu (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This study aimed to determine effect of Client Importance, Audit Tenure, AuditRotation and Audit Fee on Audit Quality with Audit Commitee as a moderatingvariable. The population in this study is a financial companies listed on the indonesiastock exchange 2013 – 2017. The population are 93 companies, this study got 31sample using purposive sampling method. The data used are secondary data andthe method of data analysis using Moderated Regression Analysis (MRA) usingsofware SPSS version 25. The results showed that Client Importance and Audit Feeeffect on Audit Quality. Audit Tenure and Audit Rotation has no effect on AuditQuality. The Audit Comittee is unable to moderate Client Importance, Audit Tenure,Audit Rotation and Audit Fee on Audit Quality.